Survival After Lobectomy vs. Sublobar Resection for Stage IA Large-Cell Neuroendocrine Carcinoma of the Lung: A Population-Based Study - Yu, Xiangyang; Zhang, Mengqi; Wang, Feifei; Guo, Xiaotong; Ma, Kai; Wang, Lixu; Zhao, Hongbo; Xiao, Hua; Huang, Chujian; Du, Longde; Jia, Ran; Yang, Yikun; et al. (Frontiers in Surgery, 2022)
Objective: Due to the low incidence of pulmonary large cell neuroendocrine carcinoma (LCNEC), the survival analysis for comparing lobectomy and sublobar resection (SLR) for stage IA LCNEC remains scarce. Methods: Patients diagnosed with pathological stage IA LCNEC between 1998 and 2016 were extracted from the Survenillance, Epidemiology, and End Results (SEER) database. The oncological outcomes were cancer-specific survival (CSS) and overall survival (OS). Kaplan-Meier analysis and Cox multivariate analysis were used to identify the independent prognostic factors for OS and CSS. Furthermore, propensity score matching (PSM) was performed between SLR and lobectomy to adjust the confounding factors. Results: A total of 308 patients with stage IA LCNEC met the inclusion criteria: 229 patients (74.4%) received lobectomy and 79 patients (25.6%) received SLR. Patients who underwent SLR were older (P<0.001), had smaller tumor size (P=0.010) and less lymph nodes dissection (P<0.001). The 5-year CSS and OS rates were 56.5% and 42.9% for SLR, and 67.8% and 55.7% for lobectomy, respectively (P=0.037 and 0.019, respectively). However, multivariate analysis did not identify any differences between SLR group and lobectomy group in CSS (P=0.135) and OS (P=0.285); and the PSM also supported these results. In addition, age at diagnosis and laterality of tumor were identified as significant predictors for CSS and OS, whereas the number of lymph nodes dissection was a significant predictor for CSS. Conclusions: Although SLR is not inferior to lobectomy in terms of oncological outcomes for patients with stage IA LCNEC, more lymph nodes can be dissected or sampled during lobectomy. Lobectomy should still be considered as a standard procedure for patients with early-stage LCNEC who are able to withstand lobectomy.